2023
DOI: 10.3389/fmolb.2023.1266243
|View full text |Cite|
|
Sign up to set email alerts
|

Sestrin2 protects against hypoxic nerve injury by regulating mitophagy through SESN2/AMPK pathway

Cunyao Pan,
Chongyi Ai,
Lanlan Liang
et al.

Abstract: Hypoxia induced by high altitude can lead to severe neurological dysfunction. Mitophagy is known to play a crucial role in hypoxic nerve injury. However, the regulatory mechanism of mitophagy during this injury remains unclear. Recent studies have highlighted the role of Sestrin2 (SESN2), an evolutionarily conserved stress-inducible protein against acute hypoxia. Our study demonstrated that hypoxia treatment increased SESN2 expression and activated mitophagy in PC12 cells. Furthermore, the knock-out of Sesn2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Meanwhile, Nrf2 translocates to the cell nucleus, binding to the antioxidant response element (ARE), thereby activating the expression of antioxidative and detoxifying genes [ 54 ]. Moreover, studies have shown that hypoxic stress also can induce mitochondrial autophagy mediated by BNIP3 and FUNDC1, further alleviating oxidative damage caused by ROSs [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Nrf2 translocates to the cell nucleus, binding to the antioxidant response element (ARE), thereby activating the expression of antioxidative and detoxifying genes [ 54 ]. Moreover, studies have shown that hypoxic stress also can induce mitochondrial autophagy mediated by BNIP3 and FUNDC1, further alleviating oxidative damage caused by ROSs [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%